Geospatial Abduction Principles and Practice - Shakarian, Paulo; Subrahmanian, V. S.; SpringerLink (Online service) (New York, NY : Springer New York, 2011)
None
Introduction -- Point-based Geospatial Abduction -- Region-Based Geospatial Abduction -- Geospatial Abduction with Adaptive Adversaries -- Two Real-World Geospatial Abduction Applications -- Index.
Keywords: Computer science; Information theory; Data mining; Artificial intelligence; Geographical information systems; Computer Science; Artificial Intelligence (incl. Robotics).; Math Applications in Computer Science; Geographical Information Systems/Cartography.; Data Mining and Knowledge Discovery; Theory of Computation